A kinetic model for vessel-encoded dynamic angiography with arterial spin labeling. - Okell, T; Chappell, M; Schulz, U; Jezzard, P (2012)
The ability to visualize blood flow in a vessel-selective manner is of importance in a range of cerebrovascular diseases. Conventional X-ray methods are invasive and carry risks to the patient. Recently, a noninvasive dynamic angiographic MRI-based technique has been proposed using vessel-encoded pseudocontinuous arterial spin labeling, yielding vessel-selective angiograms of the four main brain-feeding arteries. In this study, a novel kinetic model for the signal evolution in such acquisitions is derived and applied to healthy volunteers and to a patient with Moya-Moya disease. The model incorporates bolus dispersion, T(1) decay and radio frequency effects and is applicable to other angiographic methods based on continuous or pseudocontinuous arterial spin labeling. The model fits the data well in all subjects and yields parametric maps relating to blood volume, arrival time, and dispersion, changes to which may indicate disease. These maps are also used to generate synthesized images of blood inflow without bias from T(1) decay and radio frequency effects, greatly improving collateral vessel visibility in the patient with Moya-Moya disease. Relative volume flow rates in downstream vessels are also quantified, showing the relative importance of each feeding artery. This framework is likely to be of use in assessing collateral blood flow in patient groups. Magn Reson Med, 2012. © 2012 Wiley Periodicals, Inc.